2020
DOI: 10.1109/tmi.2019.2930338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Objective Image Quality Metrics to Expert Radiologists’ Scoring of Diagnostic Quality of MR Images

Abstract: Image quality metrics (IQMs) such as root mean square error (RMSE) and structural similarity index (SSIM) are commonly used in the evaluation and optimization of accelerated magnetic resonance imaging (MRI) acquisition and reconstruction strategies. However, it is unknown how well these indices relate to a radiologist's perception of diagnostic image quality. In this study, we compare the image quality scores of five radiologists with the RMSE, SSIM, and other potentially useful IQMs: peak signal to noise rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 28 publications
4
81
0
Order By: Relevance
“…The authors were able to draw parallels between the quantitative and blind study results, which revealed that, in their data challenge, SSIM was a reasonable estimate for the radiologists’ ranking of the images. In contrast, Mason et al [ 71 ] found differences in their study between several image metrics and experts’ opinions on reconstructed MRI images.…”
Section: Discussionmentioning
confidence: 92%
“…The authors were able to draw parallels between the quantitative and blind study results, which revealed that, in their data challenge, SSIM was a reasonable estimate for the radiologists’ ranking of the images. In contrast, Mason et al [ 71 ] found differences in their study between several image metrics and experts’ opinions on reconstructed MRI images.…”
Section: Discussionmentioning
confidence: 92%
“…As an image processing technology, edge detection is a hotspot, and it needs to be optimized in response to the complexity of medical images and the increasing amount of information contained [ 11 , 12 ]. Compared with the classic edge detection algorithm, the improved Prewitt algorithm proposed by Sengupta et al [ 13 ] greatly shortens the image processing time.…”
Section: Introductionmentioning
confidence: 99%
“…Visual inspection of the images agrees with the quantitative results. It is known that the VIF is highly correlated with the radiologist assessment of the image quality [49]. Although the VIF values of KIGAN are higher than that of RefineGAN, if we assume that an image with VIF>0.85 is good enough to be introduced into the clinical settings, there would be almost no differences between RefineGAN and KIGAN in terms of visual quality.…”
Section: Discussionmentioning
confidence: 99%